A critical review of lexical analysis and Big Five model - Richaud de Minzi, María Cristina (2002)
In the last years the idea has resurfaced that traits can be measured in a reliable and valid and this can be useful inthe prediction of human behavior. The five-factor model appears to represent a conceptual and empirical advances in the field of personality theory. Necessary orthogonal factors (Goldberg, 1992, p. 26) to show the relationships between the descriptors of the features in English is five, and its nature can be summarized through the broad concepts of Surgency, Agreeableness, Responsibility, Emotional Stability versus neuroticism and openness to experience (John, 1990, p96) Furthermore, despite the criticisms that have been given to the model, represents a breakthrough in the field of personality assessment. This approach means a contribution to the study of personality, without being the integrative model of personality.